Time-Domain Modeling of Short Pulses Radiation with Aperture Decomposition Method - Butrym, A.Yu.; Katrich, V.A.; Kazanskiy, V.B.; Kolchigin, N.N.; Pivnenko, S.N. (Радиофизика и радиоастрономия, 2002)
This paper is dealt with a general modeling method for Time Domain analysis of aperture antenna pulse radiation. Non-synchronous excitation is the main feature of the proposed approach. We solve in a closed-form the problem of pulse radiation from the rectangular aperture with uniform amplitude distribution and linear time delay distribution (it corresponds to excitation with travelling wave). Then we use a decomposition approach to calculate pulse fields radiated by Tapered Slot Antenna. We decompose an aperture of TSA into elementary rectangular apertures with given amplitudes (taking into account wave impedance and the fact that the power exponentially decays due to radiation losses) and excitation delays. The radiated field can be obtained by totalizing the fields from each elementary aperture. Then we calculate the fields from an array of TSA in H- and E-plane. We set time delay for each antenna in the array to have the ability of steering the radiation pattern of such system. Some radiation patterns for a single TSA as well as for arrays of TSA with different time delay distribution are presented. Some physical interpretations of the obtained results are given as well. В статье описан общий метод моделирования во временной области импульсного излучения апертурных антенн. В аналитическом виде решена задача излучения импульса прямоугольной апертурой с однородным амплитудным распределением и линейным распределением задержки возбуждения (что соответствует возбуждению бегущей волной). Решение было применено для вычисления импульсного поля, излучаемого расширяющейся щелевой антенной (РЩА), с использованием декомпозиционного подхода. Апертура РЩА представляется в виде набора элементарных прямоугольных апертур с заданными задержками возбуждения и амплитудами (определенными с учетом волнового сопротивления линии и экспоненциального затухания мощности в линии, обусловленного потерями на излучение). Излученное поле можно получить как сумму полей от этих элементарных апертур. Затем мы рассчитали излучение от решетки РЩА в Н- и Е-плоскостях. Временная задержка возбуждения может быть установлена для каждого элемента массива – это дает возможность управлять диаграммой направленности подобной системы. Представлены результаты расчетов диаграмм направленности как для отдельной РЩА, так и для решетки РЩА с различными распределениями задержек возбуждения. Дано физическое объяснение полученных результатов и рекомендации по вопросам электромагнитной совместимости подобных антенных решеток. У статті описано загальний метод моделювання у часовій області імпульсного випромінювання апертурних антен. В аналітичному вигляді розв’язано задачу випромінювання імпульсу прямокутною апертурою з однорідним амплітудним розподілом та з лінійним розподілом затримки збудження (що відповідає збудженню біжучою хвилею). Розв’язок було використано для обчислення (декомпозиційним методом) імпульсного поля, яке випромінюється щілинною антеною, що розширюється (ЩАР). Апертура ЩАР розбивається на елементарні прямокутні апертури із заданими затримками збудження та амплітудами, які визначаються з урахуванням хвилевого опору лінії та експоненціального згасання потужності хвилі у лінії, зумовленого втратами на випромінювання. Випромінене поле можна отримати як суму полів від цих елементарних апертур. Далі було обчислено випромінювання від решітки ЩАР у Н- та Е- площинах. Часова затримка збудження може бути встановлена для кожного елемента – це надає можливість керувати діаграмою спрямованості такої системи. Представлено результати обчислення діаграм спрямованості як для окремої ЩАР, так і для решітки ЩАР із різними розподілами затримок збудження. Дано фізичне пояснення отриманих результатів та рекомендації щодо електромагнітної сумісності таких антенних решіток.